The absence of democracy in Aboriginal self-governance policy - Burg, Gina van den (MISC, 2016)
The protracted history of Aboriginal governance policy is ripe with frustrations among First Nations peoples and Canadian governments, the most pronounced aggravation being the federal government. Substantial resistance from Aboriginals often marks each new policy the government introduces. New policies often maintain the paternalistic attitude inherent in government initiatives, which has been very difficult for Aboriginal organizations to eradicate. Although Aboriginal governance policy is currently progressing towards a quasi-cooperative form of policy-making on both sides, this particular policy area continues to encounter significant disparities between policy actors within the Canadian government and Aboriginal organizations. Differences throughout the entire policy process hinder effective policy-making from agenda-setting/problem definition to the outcome/evaluation. (author's abstract)